Changes in Cell Abundance of Colwellia psychrerythraea 34H in Response to Perchlorate-Containing Media at Subzero Temperatures, 2021-2022 ... - Firth, Evan; Dhakar, Kusum; Junge, Karen (NSF Arctic Data Center, 2024)
Liquid water is essential to life as we know it, yet most planets and moons in our solar system have surface temperatures well below the freezing point of pure water. As part of an effort to identify potential biosignatures and biosignature targets for upcoming space-exploration life detection missions, arctic strain Colwellia psychrerythraea 34H was incubated at -1 degrees Celsius (°C) and -15°C over the course of 15 days in optimal media (half-strength marine broth 2216) and optimal media amended with perchlorate ions (Wet Chemistry Lab; WCL solution, at a 1:30 ratio). Comparative cell abundance measurements are provided in two forms - direct counts via epifluorescent microscopy and optical density at 600 nanometers (nm). This research was undertaken at the Applied Physics Laboratory at the University of Washington, Seattle between 2021 and 2022. ...